PESANTREN SEBAGAI LEMBAGA PENDIDIKAN ISLAM ASLI INDONESIA - Muhammad Yunus (Edification Journal : Pendidikan Agama Islam, 2019)
This research is qualitative research in the form of library studies. Data in this study were obtained from sources such as history books and journal articles. Data collection is conducted by summarizing, organizing and formulating expert opinions contained in the written documents of the three books, journals, articles and others. There are five elements that characterize Islamic boarding schools. These five elements are the main requirements for defining a pesantren. (1) Kiyai as leaders of Islamic boarding schools, (2) santri who live in dormitories and study with clerics (3) dormitory as residence for santri (4) recitation as a form of teaching kyai to santri, and (5) mosques as centers of education and boarding school activities.